Pemikiran Al-Maturidiyah Dalam Pemikiran Islam - Zar, Abu (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
Matudiridyah was known as a moderat school that aims to elaborate between the Muâtazilah and Asyariyah School. It was established by its founder Abu Manshur al-Maturidi. Amongst the crucial Islamic thought, Abu Manshur stood out to introduce a new paradigm of Islamic theology. He aimed at bridging the two contradicting Islamic theology school between Asyari and Muâtazilah. However, his effort was not running well due to Maturidiyah School came to frictions namely Samarkand and Bukhari. The Samarkand school tended to be in line with Muâtazilah thought, while the later tended to support Asyariyah theology.